Yield, N uptake and N utilization of early maturing, drought and striga-tolerant maize varieties under low N conditions - Kamara, A.; Ewansiha, S.U.; Tofa, A.I. (Informa UK Limited, 2019)
Performance under sub-optimal nitrogen (N) conditions, of early maturing maize cultivars bred for tolerance to drought and Striga parasitism in the Nigerian savanna is not known. This study evaluated the tolerance of selected early maturing drought and Striga-tolerant maize cultivars to low N conditions in Northern Nigeria. The cultivars were evaluated at 30 and 100 kg N ha−1. The varieties were compared with an improved maize cultivar that is not tolerant to drought and Striga. Maize grain yield was 26% higher at 100 kg N ha−1 than at 30 kg N ha−1 in 2010 and 161% higher100 kg Nha−1 than at 30 kg Nha−1 in 2011. The drought and Striga-tolerant varieties produced consistently higher yields than the non-drought-tolerant variety particularly at 30 kg Nha−1. These cultivars also accumulated higher amount of N, had higher N-uptake efficiency or N-utilization efficiency than the non-drought-tolerant variety ACR 95 TZE-COMP4 C3. Grains yield at low nitrogen rate was associated with high ears m−2, high dry matter accumulation, high grains m−2, suggesting that these traits are linked to low-N tolerance. The good performance of the drought-tolerant maize varieties under low N suggests that varieties developed for drought tolerance may be tolerant to low-N conditions.